(untitled) (Architecture Image Studies, 2026)
The global landscape of higher education has witnessed a significant surge in international student mobility, with Chinese students representing the largest cohort worldwide. Thailand has emerged as an increasingly attractive destination for these students, particularly between 2023 and 2025. This article synthesizes existing literature and analytical findings to propose practical guidelines for enhancing lifelong learning (LLL) among Chinese students in Thailand. Drawing upon theoretical frameworks such as Andragogy, Social Cognitive Theory, Acculturation Theory, and Human Capital Theory, the paper identifies key facilitators and barriers to LLL engagement. The proposed guidelines offer actionable recommendations for Thai higher education institutions, Chinese students, and policymakers, aiming to foster a robust LLL mindset, cultivate essential skills, and maximize the overall benefits of their international educational experience.